2022
DOI: 10.1097/jom.0000000000002750
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Suicide and Differences in Attachment Styles and Resilience Among Treatment-Seeking First-Responder Subtypes

Abstract: Objective: To identify the predictors of suicide for firefighters (FFs), emergency medical technicians (EMTs), and law enforcement officers (LEOs). Methods: We used baseline data from FFs/EMTs (n = 69) and LEOs (n = 81) to investigate the unique predictors for both first-responder subtypes. We conducted confirmatory factor analysis on validated assessments of posttraumatic stress disorder (PTSD) and depression. Measures of attachment, resilience, PTSD, depression, generalized anxiety, trauma history, and subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Among treatment-seeking FRs, 25.3% were categorized as secure, 19% dismissive, 25.3% preoccupied, and 30.4% as fearful (Schuman et al, unpulished data, 2022b). Comparing LEOs and FFs/EMTs, LEOs were 233% times more likely to be securely attached 58 . Also, LEOs were 62% more likely to not be classified as preoccupied compared with FFs/EMTs 58 .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Among treatment-seeking FRs, 25.3% were categorized as secure, 19% dismissive, 25.3% preoccupied, and 30.4% as fearful (Schuman et al, unpulished data, 2022b). Comparing LEOs and FFs/EMTs, LEOs were 233% times more likely to be securely attached 58 . Also, LEOs were 62% more likely to not be classified as preoccupied compared with FFs/EMTs 58 .…”
Section: Discussionmentioning
confidence: 95%
“…58 Also, LEOs were 62% more likely to not be classified as preoccupied compared with FFs/EMTs. 58 In a sample of treatment-seeking veterans, 84 researchers found that attachment avoidance and attachment anxiety might be working as a reciprocal feedback loop between PTSD and suicidality as others have hypothesized. 85 Of FRs at baseline (before the assignment of a treating clinician), when categorizing attachment in its nominal classifications, FRs with secure attachment had the lowest PTSD, suicidality, depression, and generalized anxiety scores but also had the highest resilience scores compared with dismissive, preoccupied, and fearfully attached participants.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations